2017
DOI: 10.1053/j.gastro.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rate of Adenoma Detection Associates With Reduced Risk of Colorectal Cancer and Death

Abstract: In a prospective study of individuals who underwent screening colonoscopy within a National Colorectal Cancer Screening Program, we associated increased ADR with a reduced risk of interval colorectal cancer and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
301
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(325 citation statements)
references
References 23 publications
4
301
2
7
Order By: Relevance
“…If this holds true, our question now is whether increasing the observation time really helps improve the performance of screening endoscopy. In a recent study on colonoscopy, increased rates of adenoma detection were revealed to be associated with reduced risk of colorectal cancer and mortality (15). It may be hoped that subsequent studies will suggest that prolonged observation time in gastric cancer screening leads to an increase in the detection rate of gastric neoplasms.…”
mentioning
confidence: 99%
“…If this holds true, our question now is whether increasing the observation time really helps improve the performance of screening endoscopy. In a recent study on colonoscopy, increased rates of adenoma detection were revealed to be associated with reduced risk of colorectal cancer and mortality (15). It may be hoped that subsequent studies will suggest that prolonged observation time in gastric cancer screening leads to an increase in the detection rate of gastric neoplasms.…”
mentioning
confidence: 99%
“…Given this discrepancy it is possible that a similar study reproduced in the United States would not produce quite as dramatic results, however, the data demonstrates quite clearly the benefit not only that higher endoscopist ADRs convey to decrease risk of interval CRC but also the effectiveness of regular feedback on ADR. Multiple studies have shown that it is possible to affect ADR by regular feedback and monitoring (9,11,15) and Kaminski's study takes this one, important, step further to show the clinically relevant benefit this feedback has on our patients by decreasing the risk of interval colon cancer and death (13). Still uncertain remains the question of the most effective method to improve ADR: is it written feedback, direct observation by 'high detectors' of their 'low detector' colleagues, innovative technologies to assist in ADR such as alternate-view scopes, supplemental colonoscope attachments, chromoendoscopy, computer aided programs?…”
Section: Editorialmentioning
confidence: 99%
“…The proof is in the pudding: improving adenoma detection rates reduces interval colon cancer development quintile (ADR >24.5%), the adjusted hazard ratio for interval CRC was 0.27 (95% CI, 0.12-0.63 P=0.003) which translates into a reduction in the rate of interval cancer from 25.3 cases per 100,000 patient-years to 7.1 cases per 100,000 patient-years (13). Interestingly, and notably, the risk for interval CRC appears to be most improved when endoscopists' ADR rose to the highest quintile whereas there is only a negligible effect when ADR improved to/ maintained within the third quintile (ADR 15.1-19.2%).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further reinforced with the study by Kaminski et al, that showed an increased ADR resulted in an adjusted hazard ratio for interval CRC of 0.63 (95% CI, 0.45-0.88; P=0.006), and for cancer death of 0.50 (95% CI, 0.27-0.95; P=0.035). This is improved versus those that did not have an increase in ADR, with a decreased adjusted hazard ratio for interval CRC of 0.27 (95% CI, 0.12-0.63; P=0.003), and for cancer death of 0.18 (95% CI, 0.06-0.56; P=0.003) (2). Improving techniques to significantly increase your ADRs will improve the care given to your patients.…”
mentioning
confidence: 98%